1983
DOI: 10.1042/cs0650491
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Uptake by Splanchnic and Leg Tissues in Man: Relative Independence of Insulin Levels

Abstract: The influence on leucine disposal of physiological alterations in plasma insulin concentrations was examined in three groups of healthy male subjects, six in each group. After an overnight fast the subjects received an intravenous infusion of either leucine (300 mumol/min for 150 min, series A), or leucine plus glucose (2.2 mmol/min, series B), or leucine, somatostatin (7 micrograms/min) and glucagon (1 ng/min, series C). Arterial concentrations of substrates and their net exchange across the splanchnic and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
2
14
0
2
Order By: Relevance
“…This concept was supported not only by the leucine kinetic data but also by the behavior of net balance of several amino acids, which was negative in muscle but positive (i.e., in the direction of net uptake) across the splanchnic bed (Table II). This latter finding is in agreement with previous observations (30,57).…”
Section: Splanchnic Protein Synthesis and Degradationsupporting
confidence: 83%
See 1 more Smart Citation
“…This concept was supported not only by the leucine kinetic data but also by the behavior of net balance of several amino acids, which was negative in muscle but positive (i.e., in the direction of net uptake) across the splanchnic bed (Table II). This latter finding is in agreement with previous observations (30,57).…”
Section: Splanchnic Protein Synthesis and Degradationsupporting
confidence: 83%
“…Splanchnic amino acid and protein turnover had been investigated previously in humans using a variety of techniques (1,4,12,13,29,30,45,46,57). In this study, we have compared splanchnic protein degradation and synthesis, net protein balance, leucine transmembrane exchange, oxidation, and bidirectional leucine interconversion with KIC with the corresponding rates measured across the kidneys and the legs in postabsorptive humans.…”
Section: Splanchnic Protein Synthesis and Degradationmentioning
confidence: 99%
“…In contrast, Eriksson et al (19) have suggested that leucine disposal is independent of plasma insulin concentrations. However, their protocol employed glucose and leucine infusions to stimulate pancreatic insulin release and the resultant hyperglycemia and elevated plasma leucine levels created a less controlled insulin stimulus than the present studies.…”
Section: Discussionmentioning
confidence: 86%
“…The important relationship between insulin and leucine metabolism is well established (1-3). In man, insulin accelerates the disposal of an exogenous load of leucine (19) and hyperinsulinemia inhibits the release of leucine from muscle (20). In vitro studies have demonstrated that insulin enhances the uptake of leucine by muscle (21), adipose tissue (22), and liver and kidney (23), and that insulin promotes protein synthesis (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in healthy subjects glucose infusion did not alter duodenal protein synthesis 3 or splanchnic amino acid balances. 4 Correspondingly, various degrees of hyperinsulinemia remained without anabolic effects in the splanchnic bed. [5][6][7] Stimulatory effects on splanchnic protein synthesis were also absent when the insulin-induced hypoaminoacidemia was prevented by simultaneous amino acid infusion.…”
mentioning
confidence: 97%